2022
DOI: 10.1155/2022/7222590
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Attenuates the Cognitive Deficits in L-Methionine-Induced Vascular Dementia in Rats

Abstract: Vascular dementia (VaD) is the second most prevalent type of dementia characterized by progressive cognitive deficits and is a major risk factor for the development of Alzheimer’s disease and other neurodegenerative disorders. This study is aimed at determining the potential neuroprotective effect of sitagliptin (STG) on cognitive deficits in L-methionine-induced VaD in rats and the possible underlying mechanisms. 30 adult male Wistar albino rats were divided equally ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
2
8
0
Order By: Relevance
“…As the disease progresses, patients experience progressive memory loss and emotional disorder in daily life, including communication disorder and anxiety [28][29] . In vivo study also confirms impaired discrimination index in recognition memory test [30] , which is one of the most common paradigms to assess hippocampal-dependent memory, including short-term recognition memory and long-term recognition memory [31] . In general, short-term memory only refers to the short-term storage of information, whereas long-term memories are required for remembering information [32] .…”
Section: Discussionsupporting
confidence: 70%
“…As the disease progresses, patients experience progressive memory loss and emotional disorder in daily life, including communication disorder and anxiety [28][29] . In vivo study also confirms impaired discrimination index in recognition memory test [30] , which is one of the most common paradigms to assess hippocampal-dependent memory, including short-term recognition memory and long-term recognition memory [31] . In general, short-term memory only refers to the short-term storage of information, whereas long-term memories are required for remembering information [32] .…”
Section: Discussionsupporting
confidence: 70%
“…Methionine model of AD: Treatment with L-methionine dramatically increases serum homocysteine levels and elevated homocysteine levels have been linked to oxidative stress and changes in the structure and function of cerebral blood vessels, both of which are important contributors to cerebral vascular dysfunction. It is known that oxidative stress and vascular dysfunction play a significant role in the pathology of AD and vascular dementias [43 , 44] . Memory acquisition and retrieval are significantly impaired in AD due to structural abnormalities in the cerebral capillaries, which also cause neuronal malfunction and death [44] Additionally, it has been demonstrated that hyperhomocysteinemia is neurotoxic [43] .…”
Section: Methods Detailsmentioning
confidence: 99%
“…It is known that oxidative stress and vascular dysfunction play a significant role in the pathology of AD and vascular dementias [43 , 44] . Memory acquisition and retrieval are significantly impaired in AD due to structural abnormalities in the cerebral capillaries, which also cause neuronal malfunction and death [44] Additionally, it has been demonstrated that hyperhomocysteinemia is neurotoxic [43] . This neurotoxicity is due to an excess of N-methyl-D-aspartate receptors, elevated oxidative stress, increased cholinesterase activity, tau phosphorylation and the toxicity caused by amyloid-β peptides [44] .…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being required for protein biosynthesis, Met is metabolized to generate metabolites that play key roles in a number of cellular functions (Dash et al, 2016). Although few studies have focused on blood Met levels in humans, some associations have been shown between rat models of cognitive impairment and Met levels (Alzoubi et al, 2022;Khodir et al, 2022). Met is the sole substrate of Met adenosine transferase (MAT) for SAM synthesis, whereas SAM is a universal methyl donor for various methyl transfer reactions, including the methylation of DNA, RNA, and neurotransmitters in all organisms (Selhub et al, 2010).…”
Section: Figurementioning
confidence: 99%